2020
DOI: 10.1111/bcp.14194
|View full text |Cite
|
Sign up to set email alerts
|

A randomised, factorial trial to reduce arterial stiffness independently of blood pressure: Proof of concept? The VaSera trial testing dietary nitrate and spironolactone

Abstract: Aims:To test if spironolactone or dietary nitrate from beetroot juice could reduce arterial stiffness as aortic pulse wave velocity (PWVart), a potential treatment target, independently of blood pressure. Methods:Daily spironolactone (≤50 mg) vs doxazosin (control ≤16 mg) and 70 mL beetroot juice (Beet-It ≤11 mmol nitrate) vs nitrate-depleted juice (placebo; 0 mmol nitrate) were tested in people at risk or with type-2 diabetes using a double-blind, 6-month factorial trial. Vascular indices (baseline, 12, 24 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 52 publications
2
22
0
1
Order By: Relevance
“…In addition, a very recent study (Mills et al . 2020) comparing the effects of nitrate‐containing and nitrate‐depleted ‘placebo’ BRJ in non‐pregnant adults reported no difference in SBP between these arms across the 24‐week intervention period. However, in both of these groups, peripheral BP did decrease by ∼6.5 mmHg compared with baseline SBP.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a very recent study (Mills et al . 2020) comparing the effects of nitrate‐containing and nitrate‐depleted ‘placebo’ BRJ in non‐pregnant adults reported no difference in SBP between these arms across the 24‐week intervention period. However, in both of these groups, peripheral BP did decrease by ∼6.5 mmHg compared with baseline SBP.…”
Section: Discussionmentioning
confidence: 99%
“…Similar effects were also observed when NO 3 − rich beetroot juice was co-ingested alongside folate. In another study, Mills and colleagues [ 70 ] showed that 6 months consumption of NO 3 − -rich beetroot juice (~ 11 mmol/d NO 3 − ) decreased central systolic pressure by − 2.6 mmHg. Likewise, Kapil et al [ 71 ] reported reductions in 24-h systolic and diastolic BP (7.7 and 5.2 mmHg, respectively) and improved endothelial function and arterial stiffness with 4 weeks NO 3 − -rich beetroot juice supplementation (6.4 mmol/d NO 3 − ) with no change after placebo.…”
Section: Main Textmentioning
confidence: 99%
“…Only a handful of trials have explored the medium-to longer-term effects of NO 3 − consumption (4 weeks to 6 months), usually focusing on BP or endothelial function as an outcome. Whilst not a universal finding [67,68], beneficial effects of medium-to longer-term NO 3 − supplementation protocols have been reported in some trials [69][70][71]. For example, Siervo et al [69] found that 2 months supplementation with NO 3 − -rich beetroot juice (~6.5 mmol/d NO 3 − ) decreased 24-h systolic and diastolic BP by − 10.8 and − 5.4 mmHg, respectively, in a Sub-Saharan African setting.…”
Section: Main Textmentioning
confidence: 99%
“…Пищевые нитраты, содержащиеся в овощах, снижают артериальную ригидность, что связано с их влиянием на эндотелий-зависимую вазодилатацию [10]. Доказано снижение САДао при употреблении овощей, богатых пищевыми нитратами [11]. Наши результаты подтверждают положительное влияние употребления достаточного количества овощей и фруктов на сосудистую жёсткость.…”
Section: Discussionunclassified